The Effectiveness of Problem Posing Learning by CTL Orientation Viewed from Knowladge, Skill, and Attitude - Ulantari, Desutri; Harta, Idris (Al-Jabar: Jurnal Pendidikan Matematika, 2018)
This research aimed to describe: 1) the effectiveness of the use of Problem Posing Learning by CTL orientation, 2) the effectiveness of the use of CTL lessons viewed from knowledge, skills, and students’ attitude, and 3) to compare which one is more effective between Problem Posing Learning by CTL orientation and CTL lessons viewed from knowledge, skills, and students’ attitude. The kind of this research was quasi experiment by using pretest-posttest control group design. The population of this research was the eleventh grade students of MA NW Pancor, Lombok Timur, NTB. The sample of this research was already chosen randomly. Techniques of collecting the data were test and non-test by using research instrument of knowledge test, skills test, and students’ attitude questionnaires. One sample t-test used to test the effectiveness of learning which was already used in each variable. The result of the research showed that: 1) Problem Posing Learning by CTL orientation was effective viewed from knowledge, skills and attitude students’ attitude, 2) CTL was effective viewed from knowledge, skills, and students’ attitude, and 3) there was no effectiveness difference between Problem Posing Learning by CTL orientation and CTL lessons viewed from knowledge, skills, and students’ attitude.